The Aftermath of ‘Real Existing Socialism’ in Eastern Europe
XXIX, 330 p.
Keywords: The themes in this book concern former Soviet-type societies: 1) Is the capitalist world system willing and able to absorb these newcomers or are they condemned to 'Third-worldization'? 2) Is the neoliberal advice of simultaneous political democratization and economic liberalization a viable path? 3) Is the East Asian model of authoritarianism and governed markets a better option? 4) Can the revolution of rising expectations be harnessed into a new structure of accumulation based on class polarisations? 5) Are there lessons in Chinese market-socialism? In this topical and timely collection, these questions are answered by an interdisciplinary and international team of specialists.